Applied Analysis on Electromagnetic Braking in the Vehicle Braking Energy Recovery - Tu Kun; He Ren (Jixie chuandong)
The working principle and characteristic of the braking energy recovery system are introduced.The working principle of automotive electromagnetic braking is introduced. The necessity and feasibility of electromagnetic braking applied in the braking energy recovery system are analyzed. By comparing the existing structure of electromagnetic braking applied in the braking energy recovery system,the key technology and development direction of system integration are put forward. The key research direction of integrated system are the optimization design of integrated system,braking mode switch control research and the expansion of the integrated system function.